Laser Capture Microdissection in Dentistry - Uraiwan Chokechanachaisakul; Tomoatsu Kaneko; Takashi Okiji; Reika Kaneko; Hideaki Suda; Jacques E. Nör (International Journal of Dentistry)
Laser capture microdissection (LCM) allows for the microscopic procurement of specific cell types from tissue sections that can then be used for gene expression analysis. According to the recent development of the LCM technologies and methodologies, the LCM has been used in various kinds of tissue specimens in dental research. For example, the real-time polymerase-chain reaction (PCR) can be performed from the formaldehyde-fixed, paraffin-embedded, and immunostained sections. Thus, the advance of immuno-LCM method allows us to improve the validity of molecular biological analysis and to get more accurate diagnosis in pathological field in contrast to conventional LCM. This paper is focused on the presentation and discussion of the existing literature that covers the fields of RNA analysis following LCM in dentistry.